Efeitos da estimulação colinérgica sobre aspectos morfofuncionais do coração e metabolismo cerebral em ratos SHR após infarto agudo do miocárdio - Costa, Fernando Oliveira (2020)
INTRODUCTION: Acute myocardial infarction induces local or systemic changes that generate shifts in hemodynamic, autonomic, metabolic, neuro-humoral and inflammatory responses leading to homeostatic and allostatic disruptions. Along the condition, the reflex action of both peripheral and central nervous system is playing its role. The recognition of a neuro-immune system interaction gained strenght with the cholinergic anti-inflammatory pathway moreover, that this circuit can be modulated in different ways, including pharmacological agents promoting parasympathetic stimulation in order to decrease reflex inflammatory responses. OBJECTIVE: To evaluate the actions of Pyridostigmine bromide upon the cardiovascular control of different systems, peripheral and central nervous systems involved, making use of hemodynamic, autonomic, myocardial cytokines gene expression and 18F-FDG heart and brain pet-scan in the infarcted Spontaneously Hypertensive Rat. MATERIALS AND METHODS: experimental study using SHR rats divided in 3 groups: Sham operated (n=14) (Sham), infarcted (n=19) (I) and infarcted treated with pyridostigmine (I+PY) right after infarction and for 7 days (n=19). Along the experiment, different analysis were performed: hemodynamic variables such as SBP, DBP, MAP and HR and autonomic parameters such as HRV in the time-domain (RMSSD and SDNN) and frequency-domain (LF%, HF%, LF(nu), HF(nu) LF/HF ratio were performed; Echocardiographic evaluation and arterial catheterization for cardiac morphometric and functional variables including LV area and volume, LV mass, LV systolic and diastolic functions. Besides, heart and brain 18F-FDG pet-scan images in order to measure glucose uptake (Standardized Uptake Value, SUV) metabolism. And myocardial LV tissue extraction for mRNA cytokines gene expression quantification. STATISTICS: All statistical analysis were performed with GraphPad Prism®. All data were represented as means ± the standard error of the mean (SEM), the one-way analysis of variance ANOVA was performed for differences among the groups. The normality of the data was tested with the Kolmogorov-Smirnov (KS) test. P values less than 0,05 were considered significant. Bonferroni test was used in the post-hoc analysis. RESULTS: A significant decrease was found in systolic, diastolic and mean arterial pressures in both infarcted groups (I and I+PY) as compared to Sham (I vs Sham, p=0,001);(I+PY vs Sham, p=0,001) showing the hypotensive effect of infarction not corrected by pyridostigmine. HR values between-groups were not altered. HRV in the time domain showed an increase in RMSSD in group I+PY vs I and I+PY vs Sham (RMSSD: I+PY vs Sham p=0,008 and I+PY vs I p=0,005; HRV showed a notable enhancement presenting higher values in group I+PY than in the Sham group, indicating a powerful effect of the drug. HRV in the frequency domain showed an increase in LF% (sympathetic) and a decrease in HF% (parasympathetic) in group I vs Sham, representing the sympathetic predominance over parasympathetic activity in infarction. LF(nu) value remained augmented while HF(nu) increased in group I+PY vs I (p=0,003 and p=0,001, respectively) and in group I+PY vs Sham (p=0,002 and p=0,001, respectively) improving vagal activity in the treated rat. LF/HF sympathovagal balance showed a statistically significant difference between groups I vs Sham but this difference was not perceived in the treated group against I and Sham groups. Both SPVAR and SP exhibited decreased values in group I vs Sham and in group I+PY vs Sham. This indicates that the dropping effect in SPVAR caused by the infarction did not attenuate with pyridostigmine use. The alpha-index value was augmented in the treated group vs Sham group (I+PY vs Sham p=0,026) and in the treated group vs infarcted group (I+PY vs I p=0,007), augmenting the baroreceptor sensibility. The cardiac effects of myocardial infarction were evaluated using echocardiography. Morpho-functional implications were observed on the following measures: diameters, volumes and areas of the LV were increased (systolic and diastolic); I vs Sham: LVS diam: p=0,001; LVD diam: p=0,004; LVS vol: p=0,001; LVD vol: p=0,003; LVS area: p=0,001; LVD area: p=0,021. When compared to the infarcted rats (I), the treated ones (I+PY) presented a decrease in diameter, volume and area values of the LV (systolic and diastolic); I+PY vs I: LVS diam: p=0,013; LVD diam: p=0,001; LVS vol: p=0,01; LVD vol: p=0,001; LVS area: p=0,018; LVD area: p=0,003; such values may indicate the benefits of pyridostigmine upon ventricular remodeling. Concerning the systolic volume (SV) pyridostigmine showed no significant compensating effect, for I+PY vs Sham (p=0,006) and I+PY vs IAM (p=0,048). The CO followed the decrease in the SV in the infarcted rats (I vs Sham p=0,012) and no compensation was noted with treatment. The infarcted groups showed a reduced LV ejection fraction (LVEF) (I vs Sham p=0,002; I+PY vs Sham p=0,03). On the other hand, the altered LV FAC in the infarcted group (I vs Sham p=0,001) exhibited attenuation in the treated group (I+PY vs I p=0,04) ameliorating the systolic function. The I group (I vs Sham) showed an increased E/A ratio while the treated rats had a decreased E/A ratio when compared to the infarction group (I+PY vs I p=0,017), indicating a positive effect of pyridostigmine in the diastolic function. No intergroup significant results were found in the uptake values of myocardial 18F-FDG PET-scan. Intergroup results were depicted in the brain 18F-FDG PET-scan, all differences between the infarcted groups against the Sham group (I vs Sham and I+PY vs Sham). Brain pet-scan values were different between the infarcted groups (I and I+PY vs Sham) in limbic system regions or limbic associated regions. The differences were observed in 13 of the 17 SUVs represented. 9 of the 13 SUVs are in the infarcted group: global, left and right nucleus accumbens, left and right hypothalamus, medulla, left amygdala, left entorhinal cortex and left olfactory ; 5 of the 13 SUVs are in the infarct treated group: global, left accumbens, left and right hypothalamus and medulla. Il-6, Il-10, IL-17A and TNF-α values were elevated in the infarcted treated group only (I+PY vs I and I+PY vs Sham) indicating a dual (?) effect of cardiac injury and/or pyridostigmine on the gene expression. IL-1β and IL-13 showed no differences. MCP-1, a migration and infiltration monocyte/macrophage regulatory chemokine showed no differences as well. CONCLUSION: pyridostigmine showed a modulatory effect on hemodynamic, autonomic and echocardiographic parameters, no effect on glucose myocardial glucose uptake, but an effect on glucose brain metabolism. An asymmetrical uptake in left amygdala, left entorhinal cortex and left olfactory was noted in the infarcted group as compared to the treated group. Some brain regions (4) in non-treated infarcted rats showing less glucose uptake did not show the same in rats using pyridostigmine. Finally, a significant enhancement of the left myocardial ventricle gene expression cytokines was observed in rats treated with pyridostigmine.